2012
DOI: 10.4236/jbise.2012.511078
|View full text |Cite
|
Sign up to set email alerts
|

Studies on electrical and thermal properties of dental glass ionomer cement

Abstract: A commercially available dental Glass Ionomer Cement (GIC) was studied after setting at room temperature (300 K) to understand its DC electrical conductivity, dielectric and thermal properties. The dental GIC’s are supposed to have free mobile charge carriers like F<sup>-</sup> ions. Interestingly this material loses its conductivity above 80°C and behaves like a non-polar substance. The frequency dependent dielectric studies also indicate the loss of mobile charge carriers in the samples annealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…According to our results, working length measurements obtained in teeth with proximal class II cavities restored with Chemfil Superior, showed the highest inconsistency among all. Glass ionomer cements present particular electric characteristics that vary throughout the setting process, getting stable up to 5 days after mixing (Villat et al, 2010;Babu et al, 2012). Babu et al studied the dielectric and thermal properties of these materials and found that under 80°C this material behaves as a conductor and polar substance.…”
Section: Discussionmentioning
confidence: 99%
“…According to our results, working length measurements obtained in teeth with proximal class II cavities restored with Chemfil Superior, showed the highest inconsistency among all. Glass ionomer cements present particular electric characteristics that vary throughout the setting process, getting stable up to 5 days after mixing (Villat et al, 2010;Babu et al, 2012). Babu et al studied the dielectric and thermal properties of these materials and found that under 80°C this material behaves as a conductor and polar substance.…”
Section: Discussionmentioning
confidence: 99%
“…Poppendiek et al 10 measured thermal conductivity in a large number of normal and frozen samples of biological fluids and tissues using a special unidirectional heat flow apparatus. Babu et al 11 studied a commercially accessible dental Glass Ionomer Cement by adjusting it at room temperature (300 K) for understanding its thermal properties, dielectric, and DC electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…The first report on dielectric properties of glass ionomer cements was published by Tay and Braden . Later, Watts reported a systematic investigation of glass‐polyalkenoate/resin systems by dielectric spectroscopy, but up to now there have been only a few reports on the processes in glass ionomer cements and dental composites studied by this method. In particular, most of these studies are based on the measuring of the electrical conductivity or dielectric permittivity at fixed frequency during the setting process, attributing changes to the structural modifications.…”
Section: Introductionmentioning
confidence: 99%